Physical activity as an essential aspect of integral upbringing - Anna Dobosiewicz; Bartłomiej Bach; Ewelina Litwa; Nataliia Badiuk (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
Integral upbringing of a young person is an extremely important issue. This type of upbringing consists of many different factors. Speaking of human upbringing, it is also necessary to take into account the complexity of the human person (psycho-physical-spiritual). The physical activity of a young person is one of the elements which significantly influence his integral upbringing. Sports tasks undertaken at a young age and their positive consequences will be meaningful in the adult life of a growing man.